Consolidated Gold Fields in Australia The Rise and decline of a British Mining House, 1926-1998 - Porter, Robert (ANU Press, 2020)
"Consolidated Gold Fields was a major British mining house founded by Cecil Rhodes in 1892. Diversifying from its South African gold interests, the company invested widely during the following century. This included investments in the Western Australian gold sector from the 1920s and exploration and mining activities elsewhere in Australia and the Territory of New Guinea. In the 1960s, Consolidated Gold Fields Australia (CGFA) was formed. CGFA had ambitious plans and the financial backing from London to establish itself as one of the main diversified mining companies in Australia. Investments were held in the historic Mount Lyell Mining and Railway Company, in Renison, and it was one of the first groups to develop iron ore deposits in the Pilbara of Western Australia. It also acquired a major interest in mineral sands. While the London-based Consolidated Gold Fields ceased to exist in 1989, taken over and dismembered by renowned corporate raider Hanson Plc, its Australian subsidiary, renamed Renison Goldfields Consolidated (RGC), continued for another nine years as a diversified mining group before it suffered its own corporate demise, facilitated by Hanson. CGFA and RGC were important participants in Australia's post-World War II mining sector. This book is a history of a once great British mining-finance house and its investments in Australia. Consolidated Gold Fields had a rich and broad history in Australia; its ultimate fate did not demonstrate its potential as an Australian mining company."